An orchestrating role of mitochondria in the origin and development of post-traumatic stress disorder - Lushchak, Oleh; Strilbytska, Olha; Koliada, Alexander; Storey, Kenneth B. (Frontiers in Physiology, 2023)
Post-traumatic stress disorder (PTSD) is one of the most discussed and actively researched areas in medicine, psychiatry, neurophysiology, biochemistry and rehabilitation over the last decades. Multiple causes can trigger PTSD. Humans subjected to violence, participants in hostilities, victims of terrorist attacks, physical or psychological persecution, witnessing scenes of cruelty, survival of natural disasters, and more, can strongly affect both children and adults. Pathological features of PTSD that are manifested at molecular, cellular and whole-organism levels must be clearly understood for successful diagnosis, management, and minimizing of long-term outcomes associated with PTSD. This article summarizes existing data on different PTSD causes and symptoms, as well as effects on homeostasis, genetic instability, behavior, neurohumoral balance, and personal psychic stability. In particular, we highlight a key role of mitochondria and oxidative stress development in the severity and curability of PTSD. Excessive or prolonged exposure to traumatic factors can cause irreversible mitochondrial damage, leading to cell death. This review underlines the exceptional importance of data integration about the mechanisms and functions of the mitochondrial stress response to develop a three-dimensional picture of the pathology or PTSD and develop a comprehensive, universal, multifaceted, and effective strategy of managing or curing PTSD.